Digital Support and Human Touch: A Strategic Combination to Enhance Students' Learning Motivation - Sri Andini; Ratih Amelia; Loly; Wily Julitawaty; Muhammad Fathoni (Yayasan Bina Bisnis Nusantara Medan, 2025)
This study aims to analyze the role of computer laboratory facilities and staff services in influencing the learning motivation of students in the Informatics Management Program at Ganesha Polytechnic Medan. The research employed a qualitative method with observation-based questionnaires as the primary instrument. The questionnaire was distributed to 20 active students enrolled in relevant courses. The findings indicate that 75% of respondents rated the quality of computer laboratory facilities as “very good,” suggesting a significant positive impact on their learning motivation. Additionally, 80% of respondents rated staff services as “good,” indicating a positive contribution to enhancing students’ motivation to learn. These findings underscore the importance of synergy between technological infrastructure and the quality of human services in fostering a conducive learning environment.